Growth and body composition of adolescents and young adults with perinatal HIV infection: a systematic review and meta-analysis - Priscila R. F. Costa; Nathalia S. Guimarães; Carlos R. N. Lira; Luana O. Leite; Rita de Cássia Ribeiro da Silva; Maurício L. Barreto; Enny S. Paixão (BMC Public Health)
Abstract Introduction Approximately 1.3 million pregnancies are exposed to HIV perinatally each year, with transmission rates ranging from 4 to 21%, despite 85% antiretroviral therapy (ART) coverage among pregnant women. While ART has significantly reduced mother-to-child transmission, recent studies indicate an increased risk of chronic conditions among perinatally HIV-infected youth. There is a critical need for further research on the growth and health of these populations to inform effective health interventions. Therefore, the aim of this study is to critically evaluate observational research assessing the growth and body composition of perinatally HIV-infected adolescents and young adults. Methods We conducted a systematic review using the MEDLINE (by PubMed), Embase, Central (by Cochrane Library), Latin American and Caribbean Health Science Information (LILACS) and Web of Science databases. The initial search was conducted on November 24, 2022, and updated on June 3, 2024. We included cohort studies that evaluated perinatally HIV-infected adolescents (aged 10 to 19 years) and young adults (aged 20 to 24 years). A meta-analysis was performed to estimate the prevalence of stunting (HAZ < -2) and underweight (BAZ < -2). Additionally, we conducted meta-analyses for the mean values of HAZ and BAZ in the population after the follow-up period, as well as for the mean change in HAZ and BAZ post-follow-up. Results Our search strategy retrieved 11,017 documents. After excluding duplicates, we analyzed 9,273 titles and abstracts. A full-text review of the remaining 87 records was conducted. Following the updated search, we identified 6 publications from 4 studies, resulting in a total of 14 studies and 16 publications. Nine studies focused exclusively on adolescents, while three evaluated both children and adolescents, and three included both adolescents and young adults. We estimated a prevalence of stunting at 26% (95% CI: 0.23–0.29) and underweight at 14% (95% CI: 0.12–0.17). In this population, the mean HAZ was -1.58 (95% CI: -1.90; -1.27), and the mean BAZ was -0.34 (95% CI: -0.61; -0.06). Additionally, we identified an increase of 0.55 (95% CI: 0.07; 1.03) in mean HAZ and 0.12 (95% CI: -0.56; 0.79) in mean BAZ after the follow-up period. Conclusions Our study highlights significant growth and body composition challenges among perinatally HIV-infected adolescents and young adults, with concerning rates of stunting and underweight. Although there was a modest increase in height-for-age, persistent challenges in achieving optimal growth remain. The slight improvement in BMI is insufficient to fully address underweight concerns. The limited number of studies and their inherent limitations restrict the ability to draw consistent conclusions regarding the effects and magnitude of exposure on anthropometric outcomes. Further research is needed to better elucidate these relationships. Trial registration CRD42022372837.